2016
DOI: 10.1093/hmg/ddw198
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of neural crest-derived phenotypes in a zebrafish CHARGE model by Sox10 downregulation

Abstract: CHD7 mutations are implicated in a majority of cases of the congenital disorder, CHARGE syndrome. CHARGE, an autosomal dominant syndrome, is known to affect multiple tissues including eye, heart, ear, craniofacial nerves and skeleton and genital organs. Using a morpholino-antisense-oligonucleotide-based zebrafish model for CHARGE syndrome, we uncover a complex spectrum of abnormalities in the neural crest and the crest-derived cell types. We report for the first time, defects in myelinating Schwann cells, ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 83 publications
1
53
0
Order By: Relevance
“…B,D,F,H). Previous work employing chd7 morphant zebrafish showed a much more marked decrease in distal enteric nerve bodies; however, the functional consequences of this observation were not explored . Interestingly, we saw a significant decrease in GI emptying at 24 h postgavage in control larvae treated with atropine (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…B,D,F,H). Previous work employing chd7 morphant zebrafish showed a much more marked decrease in distal enteric nerve bodies; however, the functional consequences of this observation were not explored . Interestingly, we saw a significant decrease in GI emptying at 24 h postgavage in control larvae treated with atropine (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…As suggested by the pattern of cardiac defects and embryology, there are multiple lines of evidence showing that CHD7 plays a critical role in neural crest cell development and presents a stereotypic example of a neurocristopathy (Pauli, Bajpai, & Borchers, ). CHD7 is known to cooperate with PBAF to control formation of neural crest cells (Bajpai et al, ) and partially regulates Sox10 deregulation in the neural crest cells (Asad et al, ) leading to the CHARGE phenotype. Downstream Semaphorin and Robo pathways are critical to neural crest development and migration and may be involved in CHD7 ‐negative CHARGE syndrome (S R Lalani et al, ; Liu, Guo, et al, ; Schulz et al, ; Ufartes et al, ).…”
Section: Patterns Of Congenital Heart Disease In Chargementioning
confidence: 99%
“…As suggested by the pattern of cardiac defects and embryology, there are multiple lines of evidence showing that CHD7 plays a critical role in neural crest cell development and presents a stereotypic example of a neurocristopathy (Pauli, Bajpai, & Borchers, 2017). CHD7 is known to cooperate with PBAF to control formation of neural crest cells (Bajpai et al, 2010) and partially regulates Sox10 deregulation in the neural crest cells (Asad et al, 2016) (Payne et al, 2015).…”
Section: Chd7 and Associated Genes In Cardiac Developmentmentioning
confidence: 99%
“…A study presented at the 12th International CHARGE Syndrome Conference (2015) showed that zebrafish with a knockdown of the Chd7 gene had smaller GI tracts, physically limiting the quantity of consumption compared to normal controls (Steele et al, ). A recent study looking at the neural crest‐derived phenotypes in a zebrafish model of CHARGE syndrome, showed similar results with a reduction in the number of enteric neurons and vagal neural crest cells supplying the GI tract (Asad et al, ).…”
Section: Discussionmentioning
confidence: 69%